The technoscientific imaginary: Notes for its study (Sociología y tecnociencia, 2016)
The text presents a way of dealing with the study of the imaginaries, using the theory of second generation systems. For this, is used as an example, the artificial intelligence as a type of technoscientific imaginary. Imaginary that corresponds to adjectival imaginary. Where emerge ideologies, myths and beliefs. In addition to operating as a form where are built the narratives of the reality.